Spatial distribution of synanthropic cockroaches found in Quetta, Pakistan and antibiotic‐resistant bacteria strains found in Shelfordella lateralis (Walker, 1868) (Blattodea: Blattidae). Issue 12 (24th November 2021) - Kamran, Kashif; Schapheer, Constanza; Ali, Abid; Maldonado, Ana Karina; Iqbal, Asim; Arif, Sana; Villagra, Cristian
Abstract: Synanthropic cockroaches are a public health concern, because they can carry pathogens and allergens. These insects inhabit urban spaces and must be constantly monitored in order to assess the pest emergence outbreaks. Here, we combined spatial population monitoring with microbiological testing to survey the main pest cockroach species found inside residences of the city of Quetta, Pakistan. We evaluated the distribution of pest cockroaches at two scales: landscape (neighborhood) and patch (inside houses). We found at least one of the following pest species in the 73.2% of the total residences surveyed (n = 112): Shelfordella lateralis 37.1%, Periplaneta americana 23%, Blatella germanica 16.7%, Blatta orientalis 13.4% and Polyphaga aegyptiaca 9.8%. At landscape scale, the most common was S. lateralis, presenting a clustered distribution in two sampled zones, also heavily urbanized. At indoor scale, S. lateralis were most frequently found in kitchens. When we studied the bacterial loads in this species, we found that S. lateralis carried several pathogenic bacteria. Susceptibility tests tested on these strains against 10 common formulations showed antibiotic resistance for some bacteria. For instance, Pasteurella spp was susceptible towards six antibiotics tested, while Helicobacter spp showed resistance against eight antibiotics tested. Our evidence suggests that S. lateralis have the potential to displace main cosmopolitan pests and, most concerning, also carry antibiotic‐resistant pathogenic bacteria. Considering that this emergent Asian‐native pest is now present in Europe and America, it may correspond to a relevant urban pest deserving further international public health attention.